2016
DOI: 10.1111/jsr.12467
|View full text |Cite
|
Sign up to set email alerts
|

Morningness–eveningness and daytime functioning in university students: the mediating role of sleep characteristics

Abstract: SUMMARYThe aim of this study was to explore the mediating role of sleep characteristics in the relationship between morningness-eveningness and three different aspects of daytime functioning: daytime sleepiness, depressive mood and substance use in university students. A multiple mediator model was proposed with sleep debt, poor sleep quality and bedtime delay at weekends as parallel mediators in these relationships. We analysed the data of 1052 university students aged 18-25 years who completed a modified ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 33 publications
(56 reference statements)
13
45
0
2
Order By: Relevance
“…The test-retest reliability of this single-item scale has been estimated at 0.75 across four weeks [51]. The measure has been correlated with hypothetically related variables, thus providing some evidence of construct validity [45]. Using the International Classification of Sleep Disorders, 2nd edition criteria [52], individuals who reported more than one nightmare per week (Option 7, "several times a week") formed a group with a high probability of presenting sleep disorders related to nightmares.…”
Section: Assessment Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test-retest reliability of this single-item scale has been estimated at 0.75 across four weeks [51]. The measure has been correlated with hypothetically related variables, thus providing some evidence of construct validity [45]. Using the International Classification of Sleep Disorders, 2nd edition criteria [52], individuals who reported more than one nightmare per week (Option 7, "several times a week") formed a group with a high probability of presenting sleep disorders related to nightmares.…”
Section: Assessment Toolsmentioning
confidence: 99%
“…Whilst it has been reported that women obtain higher scores on morningness [41,42], other studies have indicated that the morning cycle is more frequent in men and the evening pattern more frequent in women [43]. It is indicated that the chronotypic influence, together with a probable gender difference in the neurophysiological substratum of emotional processing, can give rise to the differential appearance of nightmares for women with the eveningness chronotype [44].Further, university students are associated with a preference for eveningness, associated with lower academic performance [45]. A recent meta-analysis of circadian preference and academic achievement showed that evening-orientated students were related to worse academic performance [46].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Compared to other chronotypes, young adult evening‐types at university also report greater daytime sleepiness (Fernández‐Mendoza et al., ). But unlike sleep debt (Bakotic et al., ), sleepiness was not found to explain mental health symptoms among non‐student young adult evening‐types (Simor, Zavecz, Palosi, Torok, & Koteles, ). The mediating role of sleepiness in the relationship between sleep (e.g., eveningness, sleep duration) and mental health is therefore unclear and has not been specifically investigated among university students.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a large proportion (70%) of university students sleep less than 8 hr (Lund, Reider, Whiting, & Prichard, ) and report increased evening preferences (Kabrita, Hajjar‐Muca, & Duffy, ). Greater sleep debt has been shown to explain the relationship between eveningness and depressive symptoms in university students (Bakotic, Radosevic‐Vidacek, & Koscec Bjelajac, ). Additionally, up to 50% of university students report daytime sleepiness (Lund et al., ; Oginska & Pokorski, ), which associates with increased risk of depression (Nyer et al., ; Regestein et al., ) and anxiety among students (Choueiry et al., ).…”
Section: Introductionmentioning
confidence: 99%